Magnetoencephalographic Imaging of Resting-State Functional Connectivity Predicts Postsurgical Neurological Outcome in Brain Gliomas - Tarapore, Phiroz E.; Martino, Juan; Guggisberg, Adrian G.; Owen, Julia; Honma, Susanne M.; Findlay, Anne; Berger, Mitchel S.; Kirsch, Heidi E.; Nagarajan, Srikantan S. (Neurosurgery, 2012)
Abstract BACKGROUND: The removal of brain tumors in perieloquent or eloquent cortex risks causing new neurological deficits in patients. The assessment of the functionality of perilesional tissue is essential to avoid postoperative neurological morbidity. OBJECTIVE: To evaluate preoperative magnetoencephalography-based functional connectivity as a predictor of short- and medium-term neurological outcome after removal of gliomas in perieloquent and eloquent areas. METHODS: Resting-state whole-brain magnetoencephalography recordings were obtained from 79 consecutive subjects with focal brain gliomas near or within motor, sensory, or language areas. Neural activity was estimated using adaptive spatial filtering. The mean imaginary coherence between voxels in and around brain tumors was compared with contralesional voxels and used as an index of their functional connectivity with the rest of the brain. The connectivity values of the tissue resected during surgery were correlated with the early (1 week postoperatively) and medium-term (6 months postoperatively) neurological morbidity. RESULTS: Patients undergoing resection of tumors with decreased functional connectivity had a 29% rate of a new neurological deficit 1 week after surgery and a 0% rate at 6-month follow-up. Patients undergoing resection of tumors with increased functional connectivity had a 60% rate of a new deficit at 1 week and a 25% rate at 6 months. CONCLUSION: Magnetoencephalography connectivity analysis gives a valuable preoperative evaluation of the functionality of the tissue surrounding tumors in perieloquent and eloquent areas. These data may be used to optimize preoperative patient counseling and surgical strategy.